Risiophlebia guentheri sp. nov. (Odonata, Libellulidae) from southeastern Indochina - Kosterin, Oleg E. (Zootaxa, 2015)
Risiophlebia guentheri sp. nov. (holotype: Cambodia, Mondulkiri Province, Dak Dam village environs, a tall grass forest swamp, 12°25' N 107°19' E, ~780 m a.s.l., 16 June 2014, RMNH), the second species in its genus, is described from Central Plateau of the Annamese Mountains. The new species is most probably separated from R. dohrni by a 1000-km gap of the range of the genus in Thailand and most of Cambodia.